2012
DOI: 10.1007/s11882-012-0306-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Responses in the Common Cold and Otitis Media

Abstract: Cytokines are a group of diverse molecules that influence the function of every organ system. They are most well studied in their effects on the immune system and their integral role in mediating inflammation. The common cold and otitis media are two such disease states, and much has been learned about the various effects of cytokines in each disease. Most often the viruses isolated include rhinovirus (RV), respiratory syncytial virus (RSV), adenovirus, coronavirus, and picornavirus. Otitis media, sinusitis, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 78 publications
(72 reference statements)
1
5
0
Order By: Relevance
“…To date, the effect of cold exposure on the predisposition to illness remains poorly understood, and better understanding of the immune responses during cold exposure and its residual effects may explain an organism's susceptibility to infection. A previous study supports the notion that induction of proinflammatory cytokines may correlate with an increased risk of upper respiratory infection [71]. Another study reported that increased cortisol secretion may also increase the susceptibility to upper respiratory infection [72].…”
Section: Discussionsupporting
confidence: 64%
“…To date, the effect of cold exposure on the predisposition to illness remains poorly understood, and better understanding of the immune responses during cold exposure and its residual effects may explain an organism's susceptibility to infection. A previous study supports the notion that induction of proinflammatory cytokines may correlate with an increased risk of upper respiratory infection [71]. Another study reported that increased cortisol secretion may also increase the susceptibility to upper respiratory infection [72].…”
Section: Discussionsupporting
confidence: 64%
“…The pathogenesis, development, severity, and clinical outcomes of AOM are largely dependent on the resident composition of the NP microbiome and immune defense and few studies have provided an understanding of how the NP microbiome and molecular immune responses might be manipulated to favor the child host (Melendi et al, 2007; Alper et al, 2009; Wine and Alper 2012). The NP is the main ecological niche of AOM pathogens and is the site of transmission for otopathogens to others (contagion).…”
Section: Discussionmentioning
confidence: 99%
“…TNF- acts as an initial inflammatory cytokine, however, subsequently regulates neutrophil and eosinophil recruitment into the lung and airspace. Its absence or inhibition has demonstrated increased susceptibility to infection in rheumatoid arthritis, prolonged infection and inability to eliminate bacteria from the middle ear in otitis media and increased risk of acquiring a serious infection in inflammatory bowel disease (Wine and Alper, 2012;Deepak et al, 2013). The test compound B2.3 showed increase in the concentration of TNF- till non-cytotoxic concentrations of 10µg/ml, suggesting that the formulation may assist in clearance of bacterial and viral infections.…”
Section: Discussionmentioning
confidence: 99%